2020
DOI: 10.1088/2053-1591/ab6123
|View full text |Cite
|
Sign up to set email alerts
|

Flacourtia indica based biogenic nanoparticles: development, characterization, and bioactivity against wound associated pathogens

Abstract: Surface engineered nanoparticles (NPs) are of great attention due to their targeted medical applications. The nature of the functionalized surface plays a vital role in achieving the required functionalities of engineered NPs. Owing to the biofilm formation capabilities of wound associated pathogens, impaired wound healing is a major complication in the medical field. In this context, herein, we report the biogenic synthesis of Flacourtia indica (FI) based NPs, i.e., FI-AgNPs using the aqueous leaf extract of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 54 publications
1
7
0
Order By: Relevance
“…The AgNPs formation from silver nitrate solution incubated with P. aeruginosa supernatant overnight at 35°C was demonstrated by the color change of the reaction mixture to brown. The UV-Vis spectrometry exhibited the maximum absorption of the AgNPs at 455 nm Figure 1(a), which was consistent with the recorded range at 400-475 nm of AgNPs synthesized by various bioreductant such as bacterial supernatant (Abo-State & Partila, 2015Razack et al, 2016;Abo-State et al, 2017;Hussein et al, 2020a), fungal filtrates (Gudikandula et al, 2017), algal extracts (Abdel-Raouf et al, 2017;Arévalo-Gallegos et al, 2018) or plant extracts (Tripathi et al, 2017;Tahir et al, 2018;Ahmad et al, 2020). The AFM image suggested the spherical shape of the AgNPs with a size range of 6-12 nm, monodispersed Figure 1(b).…”
Section: Biosynthesis and Characterizations Of Agnpssupporting
confidence: 77%
“…The AgNPs formation from silver nitrate solution incubated with P. aeruginosa supernatant overnight at 35°C was demonstrated by the color change of the reaction mixture to brown. The UV-Vis spectrometry exhibited the maximum absorption of the AgNPs at 455 nm Figure 1(a), which was consistent with the recorded range at 400-475 nm of AgNPs synthesized by various bioreductant such as bacterial supernatant (Abo-State & Partila, 2015Razack et al, 2016;Abo-State et al, 2017;Hussein et al, 2020a), fungal filtrates (Gudikandula et al, 2017), algal extracts (Abdel-Raouf et al, 2017;Arévalo-Gallegos et al, 2018) or plant extracts (Tripathi et al, 2017;Tahir et al, 2018;Ahmad et al, 2020). The AFM image suggested the spherical shape of the AgNPs with a size range of 6-12 nm, monodispersed Figure 1(b).…”
Section: Biosynthesis and Characterizations Of Agnpssupporting
confidence: 77%
“…Indeed, P. aeruginosa showed the most resistant biofilm to AgNPs treatment. This finding could be explained by studies of Ahmad et al (2020). These researchers reported that AgNPs synthesized with Flacourtia indica did not show biofilm inhibition activity at doses 15-30 µg/mL, whereas a strong biofilm inhibition was observed at a concentration of 100 µg/mL and Pseudomonas aeruginosa (ETPS11) was the most resistant as they appeared as a weak biofilm producer.…”
Section: Discussionmentioning
confidence: 99%
“…Silver nanoparticles strong antimicrobial effects have been shown in many applications as antibacterial textiles, medical devices coatings, home appliances product, and many cosmetics products due to its antibiofilm activities against different pathogenic bacteria such as Salmonella, Pseudomonas, Staphylococcus , and E. coli (Singh et al, 2018 ). This activity against bacterial biofilm has been broadly recognized (Markowska et al, 2013 ), especially, these activities by plant or microbial biosynthesized nanoparticles (Thuptimdang et al, 2015 ; Singh et al, 2018 ; Ahmad et al, 2020 ). In spite of all published reports that proved the AgNPs antibacterial and antibiofilm actions, the silver nanoparticles antibacterial mechanisms were not fully investigated, and the fact that they act against bacteria is not fully explained (Yassin et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…The dried bark of this tree is conventionally used in Pakistan for improving oral hygiene and promoting teeth brightening. Earlier studies reported the antimicrobial activity of this plant against bacteria and fungi that may be due to the presence of polyphenols 1,2,[9][10][11][12][13][14][15] .…”
Section: Discussionmentioning
confidence: 99%
“…It belongs to juglandaceae and has the scientific name Juglans regia. J. regia is a medicinal plant that has been extensively used in traditional medicine for a wide array of ailments [8][9][10][11] . Tamarix aphylla (L.) Karst., is another important medicinal plant and belong to the Tamaricaceae family.…”
Section: Introductionmentioning
confidence: 99%